TEACHERS’ PERCEPTION ON THE USE OF DISNEY MOVIES AS ENGLISH LANGUAGE TEACHING MEDIA FOR YOUNG LEARNERS - Zulfatul Mubarokah; Wiwin Indiarti; Arin Inayah (LUNAR, 2022)
This research is a descriptive study of teachers’ perception using descriptive-qualitative. This research airmed to describe teachers’ perception on the use of Disney movies as English language teaching media for young learners. The researcher used interview to collect the data. There are three activities for the analysis of data, namely: data reduction, data display and conclusion drawing. The research results that the teachers mostly gave positive perception about the use of Frozen II as ELT media. They perceived Frozen II as suitable and recommended ELT media in teaching listening for young learners since it fulfills 4 functions of ELT media, namely; a) attentive, b) affective, c) cognitive, and d) compensatory functions. Therefore, there are some benefits of using Frozen II as ELT Media for young learners. First, students’ learning enthusiasm will increase. Second, Frozen II is appropriate ELT media that make the lesson clearer. Third, the use of Frozen II as ELT media avoid students’ boredom. Forth, by using Frozen II students can do different learning activities than usual.